A Rare Side Effect of Ritodrine Hydrochloride in the Treatment of Preterm Labor: A Case Report - Şimşek, Mehmet; Kurşun, Sinan; Mendilcioğlu, İnanç; Akar, Münire; Trak, Bilal (Gynecology Obstetrics & Reproductive Medicine, 2006)
A patient at the 29th week of gestation was hospitalized because of preterm labor and treated with intravenous ritodrine hydrochloride. After greater than 2 weeks of therapy erythematic maculopapular pruritic lesions appeared initially on the f orearms and later extended to extremities and the rest of the body. Cutaneous side effects have been descripted rarely in the literature. We encountered a case of erythema multiforme in the treatment of preterm labor with ritodrine hy drochloride.